Effects of ventilation modes on the concentrations of Particulate Matter (PM2.5) and indoor temperature inside vehicle cabin during mobile conditions / Noor Hafiz Noordin, Azli Abd Razak and Qi Jie Kwong - Noordin, Noor Hafiz; Abd Razak, Azli; Kwong, Qi Jie (Universiti Teknologi MARA, Perak, 2021)
Indoor Air Quality (IAQ) may come from various field of studies and normally it is related to the air quality level inside a building. Other than building, vehicle cabin can also be considered as one of the indoor spaces and it is known as Vehicle Indoor Air Quality (VIAQ). Recently, vehicle has become one of the most important requirements for a living standard. People use vehicle to travel from one place to another without realizing the exposure to the air pollutant inside the cabin. The high exposure to the many types of pollutants may affect the human health. This study was conducted to investigate one type of pollutants which is the concentrations of Particulate Matter (PM2.5) when a vehicle is moving on the road with different ventilation modes. The data for PM2.5 concentrations and indoor temperatures were collected using direct-reading instruments such as Environmental Monitoring Instrument (EMI) and Thermal Recorder. It was found that different ventilation modes had a significant effect to the concentrations of PM2.5 and indoor temperature.